Peran Filsafat Ilmu Dalam Pendekatan Ilmiah - Regina Dalih Gandes Ivoni Lubis; Iman Setiawan Latief; Tita Nurhayati (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The philosophy of science approach involves the analysis of the basic concepts, methodologies, and assumptions underlying science. It focuses on fundamental questions regarding the nature, scope, and purpose of science. This approach provides deep philosophical insights, allowing for a better understanding of the epistimological and ontological foundations within each discipline. The purpose of this research is to uncover the conceptual and epistimological foundations of a scientific discipline. Through the philosophy of science approach, research findings can include a deep understanding of the philosophical aspects of a discipline. This can involve identifying and analyzing basic concepts, epistimological assumptions, as well as ontological considerations that form the scientific basis. The findings can illustrate how these concepts influence the formation of knowledge and practice in a field of research. These implications involve impact in understanding the epistimological and ontological underpinnings of a discipline of science. This has significant consequences for our understanding of the nature of scientific knowledge and the way research is conducted. This study aims to discuss qualitative research methods of literature study. The method used is library research, collecting data by finding sources and reconstructing from various sources such as books, journals, and existing researches.